2018
DOI: 10.2147/tcrm.s169239
|View full text |Cite
|
Sign up to set email alerts
|

An unusual successful treatment with non-sulfonamides: primary cutaneous nocardiosis caused by <em>Nocardia brasiliensis</em>

Abstract: IntroductionPrimary cutaneous nocardiosis is a rare suppurative or granulomatous inflammation disease caused by Nocardia infection. Because of nonspecific clinical findings, it is always misdiagnosed as common pyogenic infection. Sulfonamides have been the standard treatment for nocardiosis, but the outcome is always poor due to the high rates of misdiagnosis and refractoriness of the disease.Cases presentationsThe presented cases are patients of acute suppurative cutaneous infection without involvement of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Nocardia can spread to almost all parts of the body through the blood from the lungs (especially the upper lobes of the lungs) or infected areas of the skin. As inhalation is the main route of transmission for Nocardia , the respiratory tract is the most affected organ, followed by the CNS, skin and soft tissue, kidneys, and peritoneum [ 19 , 20 , 21 ]. The symptoms of CNS infection include headache, meningeal irritations, seizures, and focal neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Nocardia can spread to almost all parts of the body through the blood from the lungs (especially the upper lobes of the lungs) or infected areas of the skin. As inhalation is the main route of transmission for Nocardia , the respiratory tract is the most affected organ, followed by the CNS, skin and soft tissue, kidneys, and peritoneum [ 19 , 20 , 21 ]. The symptoms of CNS infection include headache, meningeal irritations, seizures, and focal neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…But sulfonamide resistance has been reported in some cases in recent years (Brown‐Elliott et al, ; Chen et al, ; Maraki et al, ; Uhde et al, ). Nevertheless, more studies suggested that the combined drug therapy is recommended especially in severe infection or resistant to TMP‐SMX (Baio et al, ; Brown‐Elliott et al, ; Chen, Qin, Sun, Luo, & Cheng, ; Coussement et al, ; Lebeaux et al, ; Uhde et al, ) . Combination drug treatment for infection of N. brasiliensis , especially TMP/SMX combined with minocycline or cephalosporins or imipenem treatment, may have advantages compare to single drug treatment, affording to better clinical improvement and shorter treatment periods and better prevention of recurrence (John & Wilson, ; Paredes et al, ; Uhde et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Combination drug treatment for infection of N. brasiliensis, especially TMP/SMX combined with minocycline or cephalosporins or imipenem treatment, may have advantages compare to single drug treatment, affording to better clinical improvement and shorter treatment periods and better prevention of recurrence (John & Wilson, 2012;Paredes et al, 1999;Uhde et al, 2010). Other combinations therapy includes imipenem combined with amikacin or cefotaxime, as well as combined with moxifloxacin (Chen et al, 2018;John & Wilson, 2012). So far, the optimal combination treatment regiments still have not been recommended for lacking of prospective controlled trials and individualized treatment should be considered (John & Wilson, 2012;Munoz et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…73 Skin involvement is more common with N. brasiliensis. [21][22][23][24]165 Manifestations may include pustules (►Fig. 3), abscesses, necrosis, 166 and nodular pustular pyoderma with sporotrichoid spreading 22,29,37,57,72,167,168 ; infection may extend into contiguous tissues (e.g., muscle, 169 fascia, 170 bone, 29,168 and lymphatics).…”
Section: Clinical Features Pulmonarymentioning
confidence: 99%
“…16,18 Pulmonary nocardiosis may mimic communityacquired pneumonia, and this may be more common among individuals with agricultural or outdoor occupations in developing countries. 10,12,16 Nocardiosis primarily involves the lungs, 5,[19][20][21] but skin and soft tissue infections (SSTIs), [21][22][23][24][25][26][27][28][29] central nervous system (CNS) infection (brain abscesses, meningitis), 7,[30][31][32][33][34] and dissemination 4,11,12,21,35 may occur. Given the rarity of the disease, the diagnosis and initiation of appropriate antimicrobial therapy are often delayed.…”
mentioning
confidence: 99%